Positive Correlation of Resistin with Blood Lipids in Gestational Diabetes - Z Zare; MH Meshkibaf; V Hamaitkhah; R Ranjbaran; MA Takhshid (Fasa University of Medical Sciences, 2013)
Background ;Objective: Resistin is an important adipokin, secreted from adipocytes and causes insulin resistance. Gestational diabetes (GDM) is characterized by insulin resistance in insulin target tissues. The goal of this research was to investigate whether there is a relationship among resistin and various clinical and metabolic parameters in GDM.Materials & Methods: 76 pregnant women who got the diagnosis of GDM were enrolled as the study group. 70 gestational age-matched pregnant women with normal glucose tolerance were recruited as the control group of the study. Serum resistin concentration, in addition to various metabolic and biochemical parameters, were measured in two groups.Results: Plasma resistin was not significantly different in GDM patients and subjects with normal glucose tolerance. Correlation analysis revealed that LDL cholesterol, total cholesterol and triglyceride were positively correlated with plasma resistin (P < 0.004, 0.01, and 0.02, respectively).Conclusion: Plasma resistin is correlated with insulin resistance, high serum LDL cholesterol, total cholesterol and TG in the Iranian GDM patients.